A study of menopausal symptoms and its impact on lives of Nepalese perimenopausal and postmenopausal women - Shrestha, Nira Singh Singh; Pandey, Asmita (Journal of Kathmandu Medical College, 2017)
Background: Menopausal health has not been given any consideration till the recent years in developing countries. With the improving status of women in the society, more and more women are seeking help for their menopausal problems. Objectives: The study aimed to find out the prevalence of menopausal symptoms and its impact on life of perimenopausal and postmenopausal women attending gynecology outpatient department at Kathmandu Medical College Teaching Hospital. Methods: A hospital based cross sectional study was done at Kathmandu medical college teaching hospital among 100 perimenopausal and postmenopausal women attending gynecology outpatient department in the month of August 2016. A pretested questionnaire was administered to the women selected by convenience sampling. Data was analyzed by SPSS version 20 and presented in percentage and frequency table. Results: The mean age of the women in the study population was 49.98 years(SD±6.18) and mean age at menopause was 48.02 years (SD± 2.12). Ninety four percent of the women had one or more of the menopausal symptoms. The commonest menopausal symptom was mood swings and irritability (80% and 68% respectively) followed by vasomotor symptoms like hot flashes in 42% and night sweats in 24% of the women. These symptoms interfered with the women’s daily work performances in 46% of the cases, affected family life in 28% and affected social life in 32% of the cases. Conclusion: Majority of the women have menopausal symptoms during perimenopause and postmenopausal period. These symptoms have major impact on women’s personal, social, and family lives. Journal of Kathmandu Medical College Vol. 6, No. 1, 2017, page: 4-8